Hydroxide Sludge/Hydrochar-Fe Composite Catalysts for Photo-Fenton Degradation of Dyes - Zaina Izghri; Ghizlane Enaime; Mehdi Eouarrat; Lhoussaine Chahid; Layla El Gaini; Abdelaziz Baçaoui; Abdelrani Yaacoubi (Journal of Chemistry)
The photo-Fenton oxidation process was employed to degrade methylene blue (MB) using a hydroxide sludge/hydrochar-Fe composite as a catalyst prepared by physical activation of raw hydroxide sludge from a drinking water treatment plant and hydrochar-Fe prepared by hydrothermal carbonization from two-phase olive mill waste. The prepared composite was characterized by XRD, SEM, EDS, ICP, and FT-IR. The effect of major parameters, including pH, H2O2 concentration, and a dose of composite on the removal of MB has been studied. The results indicated that the MB decolorization rate increased with the increase of H2O2 concentration and catalyst addition; however, further increase in H2O2 concentration and catalyst dosage could not result in an increase of MB removal efficiency. A high degradation of 95% was achieved within 150 min under UV light irradiation at natural pH (pH = 5), a catalyst loading of 2.5 g/L, a H2O2 dosage of 14.68 mol/L, and MB concentration of 50 mg/L. Recycling studies show a MB decolorization of 92% after three cycles and the use of the composite for the degradation of another dye (methyl orange) shows a degradation of 99%, demonstrating that this composite is a promising heterogeneous photo-Fenton catalyst for long-term removal of dyes from industrial wastewater.